MENINGKATKAN HASIL BELAJAR SISWA TENTANG MATERI MATEMATIKA BANGUN DATAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV SDN 100203 SIHUIK HUIK - Nasution, Nirwana; Sabri, Sabri; Theresia, Monica (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to determine the increase in learning outcomes in flat shape materials using the Problem Based Learning (PBL) learning model in class IV SD N 100203 Sihuik huik. The subjects in this study were the fourth grade students of SD N 100203 Sihuik huik, totaling 30 people. This research is a classroom action research conducted in two cycles, namely cycle I and cycle II, where each cycle consists of planning, action, observation, reflection. The research instrument is test questions and research sheets are test questions and observation sheets. Data collection techniques by observation and test questions and data analysis techniques by using the percentage formula same with the frequency you are looking for, the percentage is divided by the number of frequencies (number of individuals). Implementation of cycle 1 got an average score of 65% but still below the KKM score. So that cycle 2 continues with the average value being 84% with complete achievement. So the comparison of cycles 1 and 2 increases. So it can be concluded that using the Problem Based Learning (PBL) learning model can improve student learning outcomes. Keywords: Problem Based Learning (PBL) Learning Model, learning outcomes, PTK